The relationship between Idiosyncratic Risk and Stock Returns: Evidence from the UK market - YIN, ZEHUA (2013)
Uncertainty is a central topic for finance. Different asset pricing models focus on many explanatory factors that may influence asset returns. In recent years, researchers have tried to understand the relationship between idiosyncratic risk and stock returns. The negative relationship found by Ang et al. (2006) has spurred an extensive debate on this topic. Having criticized Ang’s method, Fu (2009) used a different one and found an opposite result. His result was also supported by many other researches. However, previous literature has mostly collected data from the US market. This paper aims to adopt the methods of both Ang et al. (2009) and Fu (2009) to study the relationship based on the UK data. The idiosyncratic volatilities are calculated by their two different ways beyond the Fama-French (1993) three-factor model. My result shows a significant positive relation in the UK market, consistent with Fu (2009). Further evidence suggests an insignificantly negative relation from Ang’s method.